Pola Komunikasi Interpersonal Waria dalam Menangani Laju Epidemik HIV/AIDS di LSM Kebaya Yogyakarta - Rial Wahyu Widarianto (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2021)
The phenomenon of a man whose look resembles women have long existed and happened in the society. Almost all members of society know of a man who look resembling women with the term “Waria”. Social problems faced by waria in Indonesia is a very complicated and complex. With a number of the problems faced by waria, so a number of waria that care about their people build a non-governmental organization or NGO’s. The NGO named Kebaya. NGO's Kebaya emerged following the concern of a group of warias who want to improve the living standard of warias. So, there is no discrimination or negative stigma of the warias. In enforcing the fate of warias, NGO's Kebaya concentrate to the rate of the epidemic of HIV/AIDS in Indonesia, especially in special region of Yogyakarta. The purpose in this research is to know about the pattern of communication and the way to handle the pace of the HIV/AIDS epidemic conducted by warias in the NGO's Kebaya Yogyakarta. This research in a qualitative descriptive. The purpose of descriptive research is to let readers to know what happening in the research, and certain event experienced researchers while doing the research. The collected data will be tested used a technique of triangulation for the purpose to finding validity and credibility the data. Results obtained from this research is the communication that happened between NGO's Kebaya warias with adjoins warias. In the running of socialization on the prevention and handling of the rate of the HIV/AIDS epidemic. In the process found form of communication that is interpersonal communication and in group communication. Communication was in face-to-face and with a horizontal pattern. In addition, it was known about the programs that run by NGO’s Kebaya in dealing with various problems surrounding HIV/AIDS and also issues that concerning about warias.